Efektivitas Bimbingan Kelompok Dalam Penanaman Sikap Spiritual Peserta Didik Kelas Xl SMA Negeri 2 Luwuk - tiadi, anggi; Septiani, Elvina (SELLAN : Jurnal Bimbingan dan Konseling, 2025)
This study examines the effectiveness of group guidance in cultivating spiritual attitudes among eleventh-grade students at SMA Negeri 2 Luwuk. Employing a qualitative descriptive method, this research gathered data through observation, interviews with guidance counselors and students, and document analysis. The findings indicate that group guidance is effective in enhancing the understanding and internalization of spiritual values, leading to positive changes in students’attitudes and behaviors. This is evident in increased participation in religious activities and a deeper understanding of life’s meaning and purpose. However, some students exhibited less significant changes in their spiritual attitudes and behaviors and tended to be passive in group discussions. Therefore, this study recommends the use of more interactive and engaging group guidance techniques, such as role-playing, simulation games, and structured group discussions. In addition, strong support from the school, environment, family, and other supporting factors is crucial to improve the effectiveness of the group guidance program. Keywords: Group Guidance, Students’ Spiritual Attitudes, Effectiveness,